Progressive failure analysis of low-rise timber buildings under extreme wind events using a DAD approach. Issue 182 (November 2018) - He, Jing; Pan, Fang; Cai, C.S.; Chowdhury, Arindam; Habte, Filmon
Abstract: This paper discusses the interaction of low-rise timber buildings with wind loads under significant wind events such as hurricanes. The proposed analysis methodology is capable of predicting the progressive failure of low-rise buildings as a result of the wind-structure interaction for a cost-effective design. It will also assist in evaluating the wind intensity from the observed damage state of buildings. Two deterministic finite-element (FE) models are developed using ANSYS for the full-scale numerical simulation. The first model with a simple building configuration is used for the validation of a numerical modeling methodology in the ultimate failure range. It also serves to validate the proposed progressive failure analysis process via the calibration from the corresponding wind tests that can simulate failures. Then, this analysis methodology is used to study the successive stages of damage on the second model to unveil its potential applications on a more representative residential buildings in U.S. Spatiotemporally varying wind loads are applied with the purpose of expanding the application of database-assisted design (DAD) approach from the linear range to the nonlinear range and finally to the stage-wise failures, which is a necessity of the vulnerability assessment and is critical for the damage and loss prediction for the insurance industry. Highlights: New DAD application: progressive failure of low-rise timber buildings under extreme wind events. Discusses the interaction of low-rise timber buildings with wind loads. Methodology is capable of predicting the progressive failure of low-rise buildings. Two deterministic finite-element (FE) models are developed. Expands the application of database-assisted design (DAD) approach beyond the linear range.